2010
DOI: 10.1093/eurpub/ckq145
|View full text |Cite
|
Sign up to set email alerts
|

Cycling for transport and public health: a systematic review of the effect of the environment on cycling

Abstract: Although the study identified environmental factors with positive and negative associations with cycling behaviour, many other types of environmental policies and interventions have yet to be rigorously evaluated. Policies promoting cycle lane construction appear promising but the socio-demographic distribution of their effects on physical activity is unclear. The wider impact of active transport policies on health and inequalities across Europe must be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
204
1
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(227 citation statements)
references
References 46 publications
13
204
1
9
Order By: Relevance
“…This replication also suggests the relevance of our approach of using the local density of cycling infrastructure as a meaningful basis for assessing socioeconomic barriers to cycling participation. Nevertheless, as discussed elsewhere, more high quality prospective studies are needed to provide a robust assessment of the impact of building cycling infrastructure upon cycling behavior (Pucher et al, 2010b, Fraser and Lock, 2011, Yang et al, 2010.…”
Section: Implications Of the Study With Respect To Cycling Infrastrucmentioning
confidence: 99%
See 1 more Smart Citation
“…This replication also suggests the relevance of our approach of using the local density of cycling infrastructure as a meaningful basis for assessing socioeconomic barriers to cycling participation. Nevertheless, as discussed elsewhere, more high quality prospective studies are needed to provide a robust assessment of the impact of building cycling infrastructure upon cycling behavior (Pucher et al, 2010b, Fraser and Lock, 2011, Yang et al, 2010.…”
Section: Implications Of the Study With Respect To Cycling Infrastrucmentioning
confidence: 99%
“…One recent research focus concerns the role of cycling infrastructure in supporting increased cycling rates. Although some causal effect of infrastructure upon cycling participation rates is probable, reliance on cross-sectional studies, small before-and-after studies and stated preference surveys means that the underlying evidence base is relatively weak (Fraser and Lock, 2011, Pucher et al, 2010b, Yang et al, 2010. The historical origins of cycling policy in Melbourne may offer an unusual opportunity to contribute to this debate.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown the positive effect of environmental changes on commuting behavior 12,13,14,15 . However, a large share of the evidence comes from studies in high-income countries, which may not represent the urban and sociocultural characteristics of lower-income countries like those of Latin America 3,6,7 .…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, another criterion in guidelines for systematic reviews is that authors of literature reviews should search for grey literature [33,41,55]. However, with few exceptions [14,15,38,56,57], reviews on environments and physical activity only included articles from peer-reviewed journals. Sources of grey literature could be found through databases such as PsycEXTRA (http://www.apa.org/psycextra), Open Grey (http://www.…”
Section: Publication Biasmentioning
confidence: 99%
“…The main findings were that reviews inappropriately claimed to be systematic, did not provide important methodological information, omitted large numbers of relevant studies, and reported some study results incorrectly [9]. Since then, hundreds of primary studies and dozens of literature reviews about environments and physical activity have been published [10][11][12][13][14][15][16]. Many of the new literature reviews continue to demonstrate methodological limitations that might lead to an inaccurate summary of the evidence.…”
Section: Introductionmentioning
confidence: 99%